Differential Leaf Age-Dependent Thermal Plasticity in the Keystone Seagrass Posidonia oceanica - Ruocco, Miriam; De Luca, Pasquale; Marín-Guirao, Lázaro; Procaccini, Gabriele (Frontiers in Plant Science, 2019)
Gene-expression patterns and their upstream regulatory mechanisms (e.g. epigenetic) are known to modulate plant acclimatability and thus tolerance to heat stress. Thermal plasticity and differential thermo-tolerance are recognized among different genotypes, development stages, organs or tissues of the same organ. Leaf age and lifespan have been demonstrated to strongly affect photosynthetic thermo-tolerance in terrestrial species, whereas there is no information available for marine plants (seagrasses). Here, we investigated how an intense warming event affects molecular and photo-physiological functions in the leaves of the large-sized seagrass Posidonia oceanica, at fine spatial resolution. Plants were exposed for one week at 34°C in a controlled-mesocosm system. Subsequent variations in the expression of 12 target genes and global DNA methylation level (5-mC) were evaluated in three leaf-age sections (i.e. basal, medium and high) established along the longitudinal axis of youngest, young and fully mature leaves of the shoot. Targeted genes were involved in photosynthesis, chlorophyll biosynthesis, energy dissipation mechanisms, general stress response and programmed cell death (PCD). Molecular analyses paralleled the assessment of pigment content and photosynthetic performance of the same leaf segments, as well as of plant growth inhibition under acute warming conditions. Our data revealed, for the first time, the presence of variable leaf age-dependent stress-induced epigenetic and gene-expression changes in seagrasses, underlying photo-physiological and growth responses to heat stress. Mature and young leaf tissues exhibited different strategies to withstand heat stress and thus a variable thermal plasticity. This should be taken in consideration when addressing seagrass response to warming and other stressors, especially in large-sized species, where sharp age differences are present within and among leaves, and other gradients of environmental factors (e.g. light) could be at play.